Covid-19 vaccine effectiveness during Omicron BA.2 pandemic in Shanghai: A cross-sectional study based on EMR. Issue 45 (11th November 2022) - Xu, Site; Sun, Mu
Abstract : Large-scale vaccination against the spread and mutation of COVID-19 is being implemented in many countries. We aimed to assess the effectiveness of certain vaccines (87.35% inactivated), mainly Sinovac – CoronaVac and Sinopharm (Beijing) – BBIBP-CorV, during the Omicron BA.2 pandemic by cross-sectional study. The study was conducted in a cabin hospital of Shanghai, China. A total of 1194 Covid-19 patients infected with Omicron BA.2 were enrolled and epidemiological survey information was collected from the subjects through electronic medical records and questionnaires, from March 23th to April 1st in 2022. Vaccine effectiveness was reflected by the occurrence of multi-dimensional symptoms while adjusting for confounding variables. In the unstandardized vaccinated group, the Covid-19 vaccine effectiveness of Omicron BA.2 in the male group was higher than in the female group ( P  = .0171). In the standardized vaccinated group, vaccine effectiveness in [20, 40) age group was higher than in other age groups ( P  = .0002). Adjusting for gender and age, Covid-19 vaccine effectiveness of Omicron BA.2 at the specific level was 87.42% (95% confidence interval [CI], 72.35–94.28, P  < .0001), and 62.65% (95% CI, 1.47–85.84, P  = .047) in the unstandardized vaccinated and the standardized vaccinated group, respectively. Covid-19 vaccine effectiveness of Omicron BA.2 was not apparent at the general level but remained effective for the specific symptom. Further development for the Covid-19 vaccine is necessary.